2020
DOI: 10.1287/mnsc.2019.3324
|View full text |Cite
|
Sign up to set email alerts
|

Do Corporate Social Responsibility Engagements Lead to Real Environmental, Social, and Governance Impact?

Abstract: We construct an event-based outcome measure of firm-level environmental, social, and governance (ESG) impact for public and private firms globally from 2007 to 2015 using data from RepRisk. Then we measure the societal impact of corporate social responsibility (CSR) engagements using participation in the United Nations Global Compact (UNGC) as a proxy. We demonstrate a robust and striking difference between public and private firms: whereas private firms significantly reduce their negative ESG incident levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(60 citation statements)
references
References 67 publications
1
58
0
1
Order By: Relevance
“…Compared with stakeholders-related activities, the role of shareholders-related activities is not sensitive to financialization in promoting corporate innovation. This finding is consistent with the results of Li and Wu [ 13 ], suggesting that some CSR activities are always being regarded as a kind of business strategy in high-polluting industries. In addition, the shareholders-related activities of SOEs cannot be influenced by investments in financial assets, while their stakeholders-related activities are sensitive to financialization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Compared with stakeholders-related activities, the role of shareholders-related activities is not sensitive to financialization in promoting corporate innovation. This finding is consistent with the results of Li and Wu [ 13 ], suggesting that some CSR activities are always being regarded as a kind of business strategy in high-polluting industries. In addition, the shareholders-related activities of SOEs cannot be influenced by investments in financial assets, while their stakeholders-related activities are sensitive to financialization.…”
Section: Discussionsupporting
confidence: 92%
“…In order to maximize the profits of shareholders, high-polluting firms may regard some CSR engagements as a special business strategy, which can also promote corporate performance [ 31 ]. Li and Wu pointed that there is a performance gap of CSR engagements between stakeholders-related and shareholders-related activities [ 13 ]. The findings of Cupertino et al also found this performance gap, indicating that financialization can promote the capital accumulation of firms with some social responsibility practices [ 32 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…As of April 2020, the dataset included more than 140,000 companies associated with risk incidents. This dataset has been adopted by various scholars to measure crisis (Dinner, Kushwaha, & Steenkamp, 2019;Li & Wu, 2020;Wang & Li, 2019). For example, Dinner et al (2019) used RepRisk data to measure marketing crises and examined the influence of psychic distance on MNE performance during marketing crises.…”
Section: Samplementioning
confidence: 99%
“…Sustainability and green supply chain management are very important for business operations nowadays ( Li et al, 2019 , Kalkanci and Plambeck, 2020 , Li and Wu, 2020 , Wu et al, 2020 ). United Nations’ new sustainable development agenda for 2030 has come into force since 2016, which initiates 17 sustainable development goals (SDGs).…”
Section: Introductionmentioning
confidence: 99%